Effect of the COVID-19 pandemic on the oral health and nutritional status of Japanese older adults who underwent total hip or knee arthroplasty: A 3-year single-institution retrospective cohort study. Issue 46 (18th November 2022) - Matsuda, Shinpei; Kawachi, Ichiro; Fujita, Ryousuke; Yoshida, Hisato; Oki, Hisashi; Kokubo, Yasuo; Matsumine, Akihiko; Yoshimura, Hitoshi
Abstract : The coronavirus disease 2019 (COVID-19) pandemic affected the physical and mental health, socioeconomic status, and community behavior of people worldwide. The aim of this retrospective cohort study was to analyze the impact of the COVID-19 pandemic on the oral health and nutritional status of Japanese older adults based on the results of preoperative assessment in patients who underwent total hip or knee arthroplasty under general anesthesia. This study included older adults (≧65 years) who underwent total hip or knee arthroplasty in whom orthopantomography was performed for preoperative oral health assessment, during January 2019 to December 2021. Gender, age, number of family members living together, number of teeth, body mass index, and serum total protein and serum albumin levels were collected for analysis of this study. A total of 201 patients aged 65 to 89 years participated in the study. While the COVID-19 pandemic has had no impact on the oral health status, there has been a drop in serum albumin level from the results of multivariable-adjusted regression analysis considering age, gender, number of family members, and time. The COVID-19 pandemic has affected the serum albumin level of Japanese orthopedic patients aged 65 years or older.